2011
DOI: 10.1093/ejechocard/jer045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of improvement in left ventricular ejection fraction on long-term survival in revascularized patients with ischaemic left ventricular systolic dysfunction

Abstract: Ejection fraction improvement is an independent predictor of long-term outcome in revascularized patients but viability (low-dose wall motion score) and digoxin use in follow-up are also independent predictors and add incremental prognostic value to ejection fraction improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…In addition, their patients had an EF around 30%, much lower than in both the study BUCHNER et al [1] and our own [2]. JOSHI et al [5], in a more recent study, found that an 8% threshold in EF improvement was associated with better survival. This threshold was twice the mean inter-observer difference in EF measurements and ensured that patients with such an improvement truly had significant increases in global LV systolic function.…”
Section: Natural Course Of Sleep Disordered Breathing After Acute Myocontrasting
confidence: 53%
“…In addition, their patients had an EF around 30%, much lower than in both the study BUCHNER et al [1] and our own [2]. JOSHI et al [5], in a more recent study, found that an 8% threshold in EF improvement was associated with better survival. This threshold was twice the mean inter-observer difference in EF measurements and ensured that patients with such an improvement truly had significant increases in global LV systolic function.…”
Section: Natural Course Of Sleep Disordered Breathing After Acute Myocontrasting
confidence: 53%
“…246,[259][260][261][262] The presence of 4 or 5 segments with contractile reserve, which was the definition of viability utilized in STICH, has been correlated with modest ($5%) improvement in ejection fraction that may be below the threshold of measurement variability and may also be insufficient for improvement in prognosis. 242,263 WMSI and EF assess contractile function and contractile reserve of the whole ventricle rather than limiting assessment to contractile reserve in segments with severe dysfunction. Low dose WMSI may provide incremental prognostic value to a post-revascularization increase in EF for prediction of long-term outcome.…”
Section: F Current Considerations In Assessment Of Viabilitymentioning
confidence: 99%
“…Low dose WMSI may provide incremental prognostic value to a post-revascularization increase in EF for prediction of long-term outcome. 263 Videos 30-32 (available online at www.onlinejase.com) show an example of prediction of the degree of functional recovery using low dose WMSI and EF response to dobutamine. In ischemic cardiomyopathy, the contractile reserve of remodeled segments and normal segments tethered to regions with severe dysfunction may have an impact on outcome in addition to the response of segments with stunning or hibernation.…”
Section: F Current Considerations In Assessment Of Viabilitymentioning
confidence: 99%
“…Studies have documented improved left ventricular dysfunction when yoga therapy was coupled with standard medical therapy in patients with cardiac failure. 46 Joshi et al investigated the effect of improved LVEF on the long-term prognosis of patients with ischemic left ventricular systolic dysfunction, where they have indicated that a threshold of 8% improvement in the LVEF could be considered significant for the patient survival and heart failure hospitalization even though the clinical meaningful improvement of LVEF is considered to be higher than 5% in most of the studies. 46,47 The reasons for lack of statistical significance in LVEF, as documented in previous studies, include inconsistent timing of repeat LVEF assessment, time of symptom onset to a successful intervention, anterior location of the infarct, female sex, and underestimation by the echo technician, especially in large volume chambers.…”
Section: Discussionmentioning
confidence: 99%